The impact of digital transformation towards blockchain technology application in banks to improve accounting information quality and corporate governance effectiveness - Ayman Mohammad Al Shanti; Mohammad Salim Elessa (Cogent Economics & Finance, 2023)
By combining two types of studies: theoretical and field, the study aims to explore the impact of digital transformation on the quality of accounting information and the efficacy of corporate governance through the deployment of blockchain technology in banks. The study's dimensions and variables were examined using a descriptive-analytical technique. To collect data from Jordanian banks' financial analysts, auditors of shareholders' accounts, and financial managers in the field research community, data lists were developed. For the analysis of the field research data, SPSS was used. Both the first and third hypotheses were rejected, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Neither the second nor the fourth hypotheses were accepted. In order to reap the benefits of blockchain technology in increasing the quality of accounting information and strengthening corporate governance, a digital transformation toward its application in commercial operations is suggested.
Keywords: 330; accounting information quality; banks; blockchain technology application; corporate governance effectiveness; Digital transformation; Jordan